2020
DOI: 10.1186/s12989-020-00370-2
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline silica particles cause rapid NLRP3-dependent mitochondrial depolarization and DNA damage in airway epithelial cells

Abstract: Background Respirable crystalline silica causes lung carcinomas and many thousand future cancer cases are expected in e.g. Europe. Critical questions are how silica causes genotoxicity in the respiratory epithelium and if new cases can be avoided by lowered permissible exposure levels. In this study we investigate early DNA damaging effects of low doses of silica particles in respiratory epithelial cells in vitro and in vivo in an effort to understand low-dose carcinogenic effects of silica particles. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 72 publications
(150 reference statements)
4
20
0
2
Order By: Relevance
“…All these results indicate the onset of a cytotoxic response starting at a dose of 60 µg/cm 2 Min-U-Sil5. Similar results of a low or absent cytotoxic response in A549 cells have been reported in several other studies for Min-U-Sil5 [ 39 , 40 ] or other quartz particles such as Norquartz [ 41 ], DQ12 [ 9 ], and NIST1878A [ 15 , 42 ]. In all these cases, cytotoxicity was apparent at a concentration of at least 50 µg/cm 2 , which is in line with our findings.…”
Section: Discussionsupporting
confidence: 88%
“…All these results indicate the onset of a cytotoxic response starting at a dose of 60 µg/cm 2 Min-U-Sil5. Similar results of a low or absent cytotoxic response in A549 cells have been reported in several other studies for Min-U-Sil5 [ 39 , 40 ] or other quartz particles such as Norquartz [ 41 ], DQ12 [ 9 ], and NIST1878A [ 15 , 42 ]. In all these cases, cytotoxicity was apparent at a concentration of at least 50 µg/cm 2 , which is in line with our findings.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have revealed that respirable particles lead to DNA damage once they move or remain in the pulmonary interstitium [55,56,57]. Our in vivo and in vitro study suggests that mouse AT2 cells undergo extensive stimulation and deformation during exposure to coal dust particles.…”
Section: Discussionsupporting
confidence: 49%
“…It is generally believed that the cytotoxicity of silica is attributable to the activity of reactive oxygen species (ROS) generated on the surface of silica particles [ 15 , 16 ]. ROS cause direct damage to the plasma membrane and DNA, thereby inducing cell death and tumor formation [ 17 19 ]. Given that the half-life of major ROS is relatively short (O •− 2 and 1 O 2 : 10 –6 s, OH • : 10 –9 s) [ 20 ], it is conjected that their detrimental effects are limited to cells that come into immediate contact with silica MPs.…”
Section: Discussionmentioning
confidence: 99%